Designing for sustainability transitions of aquaculture in Finland. (1st September 2018) - Mok, Luisa; Gaziulusoy, İdil
Abstract: To facilitate transitions in socio-technical systems, it is necessary to adopt a strategic and systemic perspective. The dynamics of socio-technical systems are associated with uncertainty and may yield to critical problems as the systems change and may lead to adverse results without deliberate intervention. This case study research develops a new theoretical framework to support strategic design interventions that aim to anticipate and address problems in systemic transitions by integrating two areas of knowledge – strategic design and transitions theories. The theoretical framework is applied to a case study of facilitating salmon trout aquaculture in Finland that has been reaching stalemate. The resulting design demonstrates a new kind of strategic design intervention that is neither attached only to the present-day concerns to solve only present problems nor abstracted merely to the strategic level to project only long-term visions. Rather, the Strategic Ekofish Certification concept presents new strategic design with operational importance to mitigate foreseeable problems aligning with near-future goals.